2023
DOI: 10.1021/acscatal.2c05759
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on Cumene Dealkylation over H-ZSM-5 Zeolites

Han K. Chau,
Hien D. Mai,
Abhishek Gumidyala
et al.

Abstract: The influence of water on Brønsted acid chemistry has been studied extensively recently for the conversion of oxygen-containing reactants. The effect of water on hydrocarbon transformations is far less explored and understood. Here, we show that cumene dealkylation over H-ZSM-5 zeolites is strongly influenced by the location of Brønsted acid sites and the presence of water molecules inside zeolite pores. While increasing acid site density leads to enthalpic stabilization of both adsorbed states and transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Gešvandtnerová et al 151 observed that water molecules generated from catalytic reaction could mediate proton transfer processes and strongly stabilize the π-complexes of alkenes when performing DFT calculations to explore the monomolecular mechanism of isobutanol conversion to butenes on acidic chabazite zeolite. In another typical work of Chau et al , 152 enhanced rates were observed for cumene dealkylation on H-ZSM-5 zeolites upon water co-feeding. Upon water adsorption, protons from the framework can be delocalized in the form of hydronium ion clusters and the interactions between cumene and hydronium ion clusters were proposed to result in a reaction transition state with more degrees of freedom and thus a less negative activation entropy, comparing to the condition without the presence of water.…”
Section: Roles Of Water Structures In Zeolite Catalysismentioning
confidence: 82%
See 1 more Smart Citation
“…Gešvandtnerová et al 151 observed that water molecules generated from catalytic reaction could mediate proton transfer processes and strongly stabilize the π-complexes of alkenes when performing DFT calculations to explore the monomolecular mechanism of isobutanol conversion to butenes on acidic chabazite zeolite. In another typical work of Chau et al , 152 enhanced rates were observed for cumene dealkylation on H-ZSM-5 zeolites upon water co-feeding. Upon water adsorption, protons from the framework can be delocalized in the form of hydronium ion clusters and the interactions between cumene and hydronium ion clusters were proposed to result in a reaction transition state with more degrees of freedom and thus a less negative activation entropy, comparing to the condition without the presence of water.…”
Section: Roles Of Water Structures In Zeolite Catalysismentioning
confidence: 82%
“…Above cases show that the active participation of water in catalytic reactions can be reflected by the formation/stabilization of surface intermediates and transition states, thus influencing the catalytic rates on zeolitic materials. 96,116,148–152…”
Section: Roles Of Water Structures In Zeolite Catalysismentioning
confidence: 99%